Existential Approach Counseling in Dealing with Adolescent Identity Crisis: A Literature Review - Sasrianis; Yeni Karneli; Netrawati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Identity crisis is a common problem experienced by teenagers, where they often experience confusion regarding self-meaning and life goals. This phenomenon can cause significant emotional and social distress. This research aims to review the effectiveness of counseling with an existential approach in helping teenagers face identity crises. Through a systematic literature review method, this research analyzes various studies that explore the role of existential counseling in supporting adolescent identity development. The research results show that the existential approach is effective in helping teenagers find the meaning of life, increase self-acceptance, and reduce existential anxiety. Additionally, this counseling encourages independence and personal responsibility, which are important in building a strong and healthy identity. The implications of this research indicate that an existential approach can be a useful strategy for counseling practitioners in supporting adolescents to overcome identity crises and improve their psychological well-being.